Adaptaciones LIJ de Tirant lo Blanc. - Ferrer, Lluís Ramon i. (Scripta, 2016)
This paper analyses Tirant lo Blanc narrative adaptations on Children's and Young Adults Literature. The works which have not considered the novel as a whole have been excluded, as well as other genres which have also wanted to adapt Martorell's work for the same audience. The study begins by establishing the corpus of the books. Then, a catalogue has been made in order to assess the hypotext sequences selection, the paratextual elements within each of the volumes, and the adaptation adequacy of the contents of the books to the target reader